EFFECT OF AGRICULTURAL EXTENSION DELIVERY METHODS ON ARABLE CROP FARMERS’ CROPPING SYSTEMS IN KADUNA STATE, NIGERIA - Chioma Udo NWAOBIALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study analysed effect of agricultural extension delivery methods on arable crop farmers’ cropping systems in Kaduna State, Nigeria. Purposive and multi-stage random sampling procedure was used to select 120 arable crop farmers across the state. Data were collected with a structured questionnaire and analysed using descriptive and correlation coefficient analysis. The result indicated that 57.50% of farmers were males, with mean ages of 56.20 years, mean farming experience of 39.3 years and mean farm size 'of 1.86 hectares. Extension delivery methods used by the agencies were demonstrations (88.4%), adopted village (81.5%), on – farm adaptive research (75%) and group (70%). The effective extension delivery agencies in the study were; National Agricultural Extension and Research Liaison Services (